Uji Praklinik Kombinasi Obat Herbal Kopi Pinogu (Coffea canephora var Robusta) Dan Bunga Cengkeh (Syzygium aromaticum) Terhadap Penurunan Kadar Asam Urat Pada Mencit - Moh Adam Mustapa; Muhammad Taupik; Friskawati Hanapi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Decreasing uric acid levels can be given with coffee plants Pinogu (Coffea canephora var robusta) which is combined with clove flowers (Syzygium aromaticum) as a hyperuricemia drug. This study aims to measure the effect of the combination of Pinogu coffee herbal medicine and clove flower seen from the decrease in uric acid levels of male white mice made hyperuricemia by chicken liver juice. This study uses a pure experimental design with pre and post test design. Where animals are grouped into seven groups, each group consisting of 5 male white mice. Each group was induced 1 mL / 20 g BB chicken liver juice and left for 24 hours then blood was taken after 2 hours, 3 hours and 4 hours of treatment. Group I as a negative control was given Na-CMC, group II was given allopurinol suspension 0.0538 g / kg BB, group III was given a combination of Pinogu coffee and clove flowers 0.209 g / kg BB, group IV was given a combination of Pinogu coffee and clove flower 0.39936 g / kg BB, group V was given a combination of Pinogu coffee and clove flower 0.404 g / kg BB, group VI was given a single Pinogu coffee extract 0.195 g / kg BB, and group VII was given clove flower extract 0.0140 g / kg BW. The results showed that the combination of Pinogu coffee herbal medicine (Coffea canephora var robusta) and clove flower (Syzygium romaticum) can reduce uric acid levels in male white mice (Mus musculus). The combination of Pinogu coffee and clove flower 0.209 g / kg BW gives the optimal effect of reducing blood uric acid levels in mice by 64.93%. Keywords— Gout, Pinogu Coffee, Clove Flowers